HUBUNGAN ANTARA USIA DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI PUSKESMAS KETAPANG II SAMPIT TAHUN 2017-2018 - nana Maryana (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2018)
ABSTRACTBackground: Malnutrition in mothers and infants has contributed at least 3.5 milliondeaths each year (11%) from global diseases in the world. The EHDS study furtherrevealed that women who were married less than 18 years were more likely to bemalnourished than more than 18 years. This is because marriage at an early age oftenloses children, has no plans to become a mother, and often abortion. The Ministry ofHealth's Strategic which includes examination of the Upper Arm Circumference (LILA)for K1 and K4 is 93%. SEZ events are more than 20% which is a public health problem. Research Objectives: This research aims to determine the correlation between age andthe incident of Chronic Energy Deficiency (DED) among pregnant women in Ketapang IISampit community health center year of 2017-2018. Research Method: The type of research used is analytic research with a retrospectiveapproach. Populasi in this research were 1.617 pregnant women who conducted an ANCexamination using totally sampling technique and using the Chi-Square test with a 95%confidence level Research Results: The age of respondents in Ketapang II Public Health Center did notexperience a high risk of pregnancy, namely 1,502 respondents (92.9%), and the age ofhigh risk was 115 respondents (7.1%). Respondents who were not SEZs in Ketapang IIHealth Center were 1.503 respondents (92.9%), and those who experienced SEZ were 114respondents (7.1%). Conclusion: There is a significant relationship between the relationship of age with theincidence of chronic energy deficiency in pregnant women in Ketapang II Public HealthCenter which is indicated by the ?-value: 0,000.